2009
DOI: 10.1017/s1751731109990474
|View full text |Cite
|
Sign up to set email alerts
|

Determination of standardized ileal crude protein and amino acid digestibilities in protein supplements for piglets

Abstract: The objective of the study was to determine standardized ileal digestibilities (SID) of crude protein (CP) and amino acids (AA) in six ingredients commonly used in weanling pigs diets. The ingredients consisted of extruded soybeans (SB e ), high-protein soybean meal (SBM hp ), soy protein concentrate (SPC), hydrolyzed wheat gluten (WG h ), conventional fish meal 1 (FM1) and extracted fish meal 2 (FM2 e ). Each assay feed ingredient was added to a purified cornstarch-based basal diet supplemented with casein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
6
7
4
Order By: Relevance
“…The protein SID of SBM observed in this study was higher than that observed in other studies, which have reported values between 80% and 94% (Walker et al., ; Urbaityte et al., ; Cervantes‐Pahm and Stein, ). The indispensable AAs SID of SBM observed in the present study was lower than values in weanling pigs reported by Cervantes‐Pahm and Stein ().…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The protein SID of SBM observed in this study was higher than that observed in other studies, which have reported values between 80% and 94% (Walker et al., ; Urbaityte et al., ; Cervantes‐Pahm and Stein, ). The indispensable AAs SID of SBM observed in the present study was lower than values in weanling pigs reported by Cervantes‐Pahm and Stein ().…”
Section: Discussioncontrasting
confidence: 85%
“…() and by Urbaityte et al. (), with the exception of lower values for lysine and methionine in the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…The calculi excluded crystalline amino acids (L-Lys-HCl, DL-Met, L-Thr and L-Trp) because they were considered completely digested at the end of the ileum [21,22]. …”
Section: Methodsmentioning
confidence: 99%
“…Although the use of the estimate from one endogenous protein in each experiment has been recommended to estimate the SID [39,40], it is also true that the SID has been estimated from previously published AID data and corrected with an endogenous protein that was estimated later [9,43,44] or previously [45,46]. This supports the use of a “standard” endogenous protein to correct the AID.…”
Section: Discussionmentioning
confidence: 79%